Globalisation and the Muslim Ummah: Issues, Challenges, and the Ways Out - Sule, Babayo; Yahaya, Muhammad Aminu; Ating, Rashid (IIUM Journal of Religion and Civilisational Studies, 2018)
Globalisation is a phenomenon and a process that is aspiring to transform the entire world into a single political and economic system through the rapid movement of goods and people across the planet in the most rapid speed ever witnessed in the history of mankind. This paper is a theoretical and conceptual research which investigates the dilemmas of the Muslim ummah in the era of globalisation. The problem is the way the global forces are threatening to obliterate all cultures and civilisations in favour for non-conforming Western political and economic arrangements. The research uses a qualitative method of data collection and analysis. Secondary sources are also used in the data collection. Books, journals, internet sources, and institutional reports are used for this research. The data gathered is analysed and interpreted using content analysis and thematic expressions. This research discovers that the Muslim ummah has been facing many challenges and issues, such as cultural impoverishment, educational and technological backwardness, economic emasculation, internal strife, ideological battles, and domination of the hegemonic world powers. Additionally, this research suggests that, despite the challenges faced by the Muslim ummah in the globalisation era, this process of globalisation provided many benefits to the ummah which it is utilising and should continue to utilise. This research recommends that the way out of the current predicaments of the Muslim ummah is to resort to the pure teachings of Islam, unity, diversity, and intellectual challenge, where other cultures and civilisations can be utilised through using knowledge and dialogue instead of spreading hostility and violence.